BIOLOGICALLY ACTIVE SUBSTANCES OF COMPOSITIONS BASED ON PLANTS OF THE GENUS HAPLOPHYLLUM - Ikhsanov Yerbol Saginovich; Umbetova Almagul Kengebaeva; Amangazieva Asem Talgatovna; Burasheva Gauhar Shahmanovna (Academic Scientific Journal of Chemistry, 2020)
The article presents the results of research of biologically active substances of compositions based on the plant of the genus Haplophyllum (Tuberculatum), which grows in the Bakanas district of Almaty region, Bidens (Frondosa), collected in the Enbekshikazakh district and Polygonum (Aviculare) from the territory of Tashtykara district of Almaty region. The mineral composition was studied, and the article also provides data on vitamin, amino and fatty acid compositions. Medicinal raw materials contain many compounds that are potentially harmful to the human body, these can be both mineral components, for example, salts of heavy metals, and various organic substances, both being natural metabolites of the plant and trapped in raw materials from the environment (pesticides used in agriculture or industrial emissions). The study of mineral composition was carried out using atomic absorption analysis on the basis of the center of physico-chemical methods of research and analysis (cfhma). As a result, information was obtained about the microand macronutrient composition of compositions based on a plant of the genus Haplophyllum (Tuberculatum). The content of fatty acids was determined by the GVC method and using the following chromatography conditions: carrier gas-helium, flame ionization detector, carrier gas speed 30ml / min, detector temperature 188ºC, furnace temperature 2300 C, analysis time 1 hour, steel column 0.4×3mm filled with polyethylene glycoladipinate (20%) on cellulite-545. Studies of amino acids were carried out on the amino acid analyzer "Carlo Erba", using the gzhx method, chromatography conditions: carrier gas-helium, flame ionization detector 300ºC, evaporator temperature 250ºC, on the WAW chromosome. The content of vitamins a (retinol) and (tocopherol) was determined by the fluorimetric method on the spectrofluorimeter device. Vitamin C in biological samples was determined by titrimetric method.